Psychological Mechanisms of Developing Professional Competence in Future English Language Specialists - Anusha Rathnayake; Arziqulov Hasan Normurod Ugli; Tagayeva Umida Ernazarovna (Jurnal Psikologi, 2025)
This article explores the psychological mechanisms involved in the development of professional competence among university students, particularly future English language specialists. It discusses essential strategies, conditions, and principles that facilitate this process and emphasizes the role of pedagogical and psychological support in building future professionals’competence